2020
DOI: 10.1111/all.14310
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of uric acid or IL‐1β ameliorates respiratory syncytial virus immunopathology and development of asthma

Abstract: Background Respiratory syncytial virus (RSV) affects most infants early in life and is associated with increased asthma risk. The specific mechanism remains unknown. Objective To investigate the role of uric acid (UA) and IL‐1β in RSV immunopathology and asthma predisposition. Methods Tracheal aspirates from human infants with and without RSV were collected and analyzed for pro‐IL‐1β mRNA and protein to establish a correlation in human disease. Neonatal mouse models of RSV were employed, wherein mice infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 67 publications
3
45
0
Order By: Relevance
“…Schuler et al show that uric acid and IL-1β play a role in the mechanism, and their inhibition can prevent the development of asthma after neonatal RSV infection, thus being a possible therapeutic target. 74 A prospective study suggested infants suffering from bronchiolitis at less than 6 months of age have a twice higher risk of doctor-diagnosed asthma after follow-up for 11-13 years compared to general Finnish population and that the RSV was the main reason for bronchiolitis in these infants. 75 The EAACI Influenza in Asthma Task Force performed a scoping review about the influenza burden, prevention, and treatment in asthma.…”
Section: Molecular Mechanisms In Allergic and Nonallergic Asthmamentioning
confidence: 99%
“…Schuler et al show that uric acid and IL-1β play a role in the mechanism, and their inhibition can prevent the development of asthma after neonatal RSV infection, thus being a possible therapeutic target. 74 A prospective study suggested infants suffering from bronchiolitis at less than 6 months of age have a twice higher risk of doctor-diagnosed asthma after follow-up for 11-13 years compared to general Finnish population and that the RSV was the main reason for bronchiolitis in these infants. 75 The EAACI Influenza in Asthma Task Force performed a scoping review about the influenza burden, prevention, and treatment in asthma.…”
Section: Molecular Mechanisms In Allergic and Nonallergic Asthmamentioning
confidence: 99%
“…Conversely, SUA levels are increased in infections of other systems. Respiratory syncytial virus (RSV) induces increased UA levels in mouse neonates, and the inhibition of UA by xanthine oxidase inhibitor decreases mucus production, reduces cellular in ltrates to the lungs (particularly ILC2s), and decreases type 2 immune responses [8]. UA is a biomarker of early cystic brosis lung disease [22], and high SUA is positively correlated with severe infections such as sepsis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory syncytial virus (RSV) induces increased UA levels in mouse neonates, and the inhibition of UA by xanthine oxidase inhibitor decreases mucus production, reduces cellular in ltrates to the lungs (particularly ILC2s), and decreases type 2 immune responses [8]. UA is a biomarker of early cystic brosis lung disease [22], and high SUA is positively correlated with severe infections such as sepsis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have investigated the relationship between SUA levels and in ammation (bacteria, viruses or autoimmunity), but the conclusions were inconsistent. Most studies had shown that in ammation could induce the increase of SUA, particularly when the virus invaded the respiratory system [8]. However, SUA tend to decrease during central nervous system infection [6,9].…”
Section: Introductionmentioning
confidence: 99%